Iklim Organisasi, Beban Kerja, Pengembangan Diri, dan Demotivasi Anggota Organisasi Kemahasiswaan - Andi Muh. Ahsan Rizal; Aulia Suminar Ayu (Universitas Sebelas Maret (UNS), 2024)
Demotivation is often based on a number of factors which result in disappointment and anxiety at work. This can lead to members becoming less enthusiastic or even unmotivated in any way. This of course really threatens the sustainability of student organizations, especially as there are more and more additional activity options for students besides campus organizations. This is also the phenomenon experienced by LPM Kentingan UNS, one of the organizations that offers a lot of skill development, and also the LPM organization with the most members in UNS. The aim of this research is to determine whether there is an influence between organizational climate variables, workload and self-development on the demotivation of members at LPM Kentingan UNS. It is hoped that this research will be capable. This research uses Thibaut and Kelly's social exchange theory as an approach to analyzing phenomena. The research method that will be carried out in this research is multiple linear regression analysis. The results of the research show that there is a significant influence between organizational climate, workload and self-development on demotivation among LPM Kentingan UNS members.